ROLE AND IMPORTANCE OF PSYCHOLOGICAL STABILITY IN THE PROFESSIONAL ACTIVITY OF A MILITARY SERVANT - Abdurakhmanova R. I. (Journal Park Publishing, 2023)
The article presents different views of military psychologists and scientists in the study of psychological stability of military personnel. The role and significance of psychological stability in professional activity is studied. Factors influencing its development and strengthening in the process of professional training are also indicated. The author of the article highlights the views of foreign and domestic scientists in demonstrating resilience directly in extreme situations. In this way, the conditions for its development are also studied.
Keywords: psychological stability, flexibility, self-control, military personnel, cadets, professional training, activity, analysis of theories.